Prevalence and predictors of episiotomy and perineal tear at a tertiary hospital in Port-Harcourt, Nigeria - Awoyesuku, Peter A.; John, Dickson H.; Altraide, Basil O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Despite many years of it being practiced, episiotomy has remained a controversial operation. The rate is on the decline in developed countries but remains high in developing countries. This study seeks to determine the prevalence of episiotomy and perineal tear, and to assess the associated factors, at the Rivers state university teaching hospital (RSUTH). Methods: A retrospective study over a two-year period, from 01 January 2018 to 31 December 2019, was carried out. All women who had singleton spontaneous vaginal deliveries (SVD) with episiotomy or perineal tear at the RSUTH with complete records were included, those with twin delivery and incomplete data were excluded. Data was retrieved from the birth registers and case notes using a proforma. Information on maternal age, parity, gestational age (GA), type of injury, birth weight, head circumference and Apgar scores were extracted. Data were analyzed using statistical package for the social sciences (SPSS) version 20. Results: There were 2150 vaginal deliveries, with 440 (20.5%) receiving episiotomy, while 21 (1.0%) had perineal tear. The mean age±standard deviation (SD) was 29.52±4.97 years, median parity was 1, and mean GA±SD was 37.35±1.71 weeks. The mean birth weight±SD was 3.33±0.52 kg and mean head circumference±SD was 34.76±1.90 cm. There was significant association between maternal parity and fetal birth weight with the occurrence of episiotomy and perineal tears. Conclusions: The rate of episiotomy and perineal tear was higher than recommended, with an increasing trend. The lower the parity and the higher the fetal birth weight, the likelihood to receive an episiotomy. More efforts are needed to reduce the rate.